Karakterisasi Windbelt Sebagai Generator Listrik - Nur Untoro (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
Research has been conducted to study the Windbelt as electrical generators. This research aims to study the aspect ratio of the ribbon to the ribbon flutter, the influence of stress to flutter frequency, the influence of windspeed to induction voltage, the effect of wind speed on the amplitude, wind speed relationship to flutter frequency, wind speed relationship to the power of wind belt . The results show that the higger aspect ratio required lower wind speed to flutter. Test results wind belt frequency with a fixed force of 5.88 N and wind speed 3m / s to 5.5 m / s indicates the value of fixed frequency ( 111 ± 0.2 ) Hz . This fact shows the standing wave by fluttering ribbon following the Melde’s law. Amplitude ribbons flutter initially increases with increasing wind speed, but eventually almost constant amplitude. This occurs because the elastic force who against the aerodynamic force was proportional with amplitude, so that the amplitude is fixed. Wind belt electric voltage generated increases with increasing wind speed. Wind belt electrical power is directly proportional to the wind speed.